RETRACTED ARTICLE: Gamma-radiated immunosuppressed tumor xenograft mice can be a new ideal model in cancer research - Khodayari, Hamid (Sci Rep, 2021)
Tumor xenograft models can create a high capacity to study human tumors and discover efficient therapeutic approaches. Here, we aimed to develop the gamma-radiated immunosuppressed (GIS) mice as a new kind of tumor xenograft model for biomedical studies. First, 144 mice were divided into the control and treated groups exposed by a medical Cobalt-60 apparatus in 3, 4, and 5 Gy based on the system outputs. Then, 144 BALB/c mice were divided into four groups; healthy, xenograft, radiation, and radiation + xenograft groups. The animals in the xenograft and radiation + xenograft groups have subcutaneously received 3 × 10(6) MCF-7 cells 24 h post-radiation. On 3, 7, 14, and 21 days after cell injection, the animals were sacrificed. Then, the blood samples and the spleen and tumor tissues were removed for the cellular and molecular analyses. The whole-body gamma radiation had a high immunosuppressive effect on the BALB/c mice from 1 to 21 days post-radiation. The macroscopic and histopathological observations have proved that the created clusters' tumor structure resulted in the xenograft breast tumor. There was a significant increase in tumor size after cell injection until the end of the study. Except for Treg, the spleen level of CD4, CD8, CD19, and Ly6G was significantly decreased in Xen + Rad compared to the Xen alone group on 3 and 7 days. Unlike IL-4 and IL-10, the spleen level of TGF-β, INF-γ, IL-12, and IL-17 was considerably decreased in the Xen + Rad than the Xen alone group on 3 and 7 days. The spleen expressions of the VEGF, Ki67, and Bax/Bcl-2 ratio were dramatically increased in the Xen + Rad group compared to the Xen alone on 3, 7, 14, and 21 days. Our results could confirm a new tumor xenograft model via an efficient immune-suppressive potential of the whole-body gamma radiation in mice.